A rabbit model of antegrade selective cerebral perfusion with cardioplegic arrest. (May 2016) - Zou, L; Liu, J; Zhang, H; Wu, S; Long, C; Ji, B; Yu, Z; Tang, Y; Meng, L; Wu, A
Objective: Due to the weak ascending aorta, it is extremely challenging to establish an anterograde selective cerebral perfusion (ASCP) model in rabbits, especially when cardioplegic arrest is required. Herein, the aim of this study was to establish a rabbit ASCP model with cardiac arrest being easily performed and being similar to the clinical scenario. Materials and methods: Twenty-two adult New Zealand white rabbits were selected for ASCP model establishment and another 22 rabbits were utilized for blood donation. The cardiopulmonary bypass (CPB) circuit consisted of a roller pump, a membrane oxygenator, a heat-cooler system and a blood reservoir, which were connected by silicone tubing. The total priming volume of the circuit was 70 ml. Cannulations on the right and left subclavian arteries were used for arterial inflow and cardioplegia perfusion, respectively. Venous drainage was conducted through the right atrial appendage. ASCP was initiated by clamping the innominate artery; the flow rate was maintained 10 ml/kg/minute and sustained for 60 minutes. After 120 minutes of reperfusion, the rabbits were sacrificed. The mean arterial pressure, heart rate, electrocardiogram and urine output were monitored. Arterial blood samples were analyzed at the following time points: after anesthesia, immediately after CPB, after aorta cross-clamping and cardioplegia perfusion, 5 min after the re-opening of the aorta and at CPB termination. Results: ASCP modeling was performed successfully on 18 rabbits and 4 rabbits unsuccessfully. Vital signs and blood gas indictors changed in an acceptable range throughout the experiments. One rabbit had ventricular fibrillation after re-opening of the ascending aorta. Obvious hemodilution occurred after the perfusion of cardioplegia, but the hematocrit improved after CPB termination. Conclusion: By using cannulation of the subclavian artery rather than the aorta and with a low priming volume, we established a modified rabbit model of ASCP with cardioplegic arrest. The model has excellent repeatability and operability, which is similar to the clinic process and is suitable for the study of cerebral, cardiac and renal protection.